Arterial stiffness in hypertensive and type 2 diabetes patients in Ghana: comparison of the cardio-ankle vascular index and central aortic techniques. Issue 1 (December 2016) - Yeboah, Kwame; Antwi, Daniel; Gyan, Ben; Govoni, Virginia; Mills, Charlotte; Cruickshank, J.; Amoah, Albert
Abstract Background Diabetes and hypertension increase arterial stiffness and cardiovascular events in all societies studied so far; sub-Saharan African studies are sparse. We investigated factors affecting arterial function in Ghanaians with diabetes, hypertension, both or neither. Method Testing the hypothesis that arterial stiffness would progressively increase from controls to multiply affected patients, 270 participants were stratified into those with diabetes or hypertension only, with both, or without either. Cardio-ankle vascular index (CAVI), heart–ankle pulse wave velocity (haPWV), aortic PWV (PWVao) by Arteriograph, aortic and brachial blood pressures (BP), were measured. Results In patients with both diabetes and hypertension compared with either alone, values were higher of CAVI (mean ± SD, 8.3 ± 1.2 vs 7.5 ± 1.1 and 7.4 ± 1.1 units;p < 0.05), PWVao (9.1 ± 1.4 vs 8.7 ± 1.9 and 8.1 ± 0.9 m/s;p < 0.05) and haPWV (8.5 ± 1 vs 7.9 ± 1 and 7.2 ± 0.7 m/s;p < 0.05) respectively. In multivariate analysis, age, having diabetes or hypertension and BMI were independently associated with CAVI in all participants (β = 0.49, 0.2, 0.17 and -0.2 units;p < 0.01, respectively). Independent determinants of PWVao were heart rate, systolic BP and age (β = 0.42, 0.27 and 0.22;p < 0.01), and for haPWV were systolic BP, age, BMI, diabetes and hypertension status (β = 0.46, 0.32, -0.2, 0.2 and 0.11;p < 0.01). Conclusion In this sub-Saharan setting with lesser atherosclerosis than the western world, arterial stiffness is significantly greater in patients with coexistent diabetes and hypertension but did not differ between those with either diabetes or hypertension only. Simple, reproducibly measured PWV/CAVI may offer effective and efficient targets for intervention.